Unbalanced Active Distribution Analysis with Renewable Distributed Energy Resources - Syafii Syafii; K. M. Nor (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2015)
This paper presents unbalanced active distribution system analysis with renewable distributed Energy Resources (DER). The renewable DER models have been considered are photovoltaic (PV) and Wind Turbine generation (WTG). The three-phase distribution load flow on the basis of the symmetrical components have been used in the analysis. The unbalanced active distribution system has been analized using IEEE 13 node feeder and IEEE 8500 node feeder with renewable DER units. The variation of wind speed (m/s) for WTG, solar radiation (W/m²) and temperature (°C) for PV have been simulated. The simulation results show that the proposed DER model can be used to analysis renewable DER impacts in unbalanced distribution system. The integration of renewable DER units into an existing distribution network can improve the voltage profile and reduce total system losses. The simulation results show that DERs size and location are important factors to improve voltage profile and line loss reduction.